DAMPAK KENAIKAN HARGA EKSPOR TERHADAP KINERJA SEKTOR INDUSTRI PENGOLAHAN INDONESIA - Asmara, Alla (Forum Agribisnis, 2012)
Stimulus on export prices which applied in several industries will provide substantial incentives for the development of national industri. The extent of export price incentives to promote the industri became the main question of this study. In detail, the main objectives of this study include: analyzing industri export price volatility and its impact on the performance of the manufacturing sector. The analytical method used is ARCH-GARCH model and Recursive Dynamic CGE. The results confirm that the export price volatility of several industries tends to vary over time (time varying). The export price volatility of steel industri tends to be higher than other industries. Export price volatility generally provides positive impacts on industries that experienced increasing export prices, such as: animal vegetable oils, textile, and steel.